Computed Tomography As A Guiding Tool In Thoracic Trauma Surgery: Clinical Outcomes And Challenges (The Review of Diabetic Studies, 2025)
Objective: To synthesize recent evidence (2020–2025) on the role of computed tomography (CT)—including whole-body CT and CT angiography—as a guiding tool in surgical decision-making of thoracic trauma, describing clinical outcomes and major challenges. Methods: Structured narrative review of guidelines, systematic reviews, meta-analyses, and observational studies published in the last 5 years in English/Spanish. Results: CT accelerates the identification of major thoracic lesions, optimizes the indication of interventions (e.g., endovascular repair in aortic lesions), and is associated with improvements in care flow and, in some contexts, with reduced mortality compared to selective strategies; however, uncertainties persist about benefit in all subgroups, cumulative exposure to contrast/radiation, and over-detection of incidental findings. Conclusions: CT is a diagnostic-therapeutic mainstay in modern thoracic trauma and guides critical surgical decisions; additional pragmatic studies are required by subpopulations (elderly, low-impact polytrauma, penetrating trauma) and dose and contrast optimization protocols.